FORMULASI DAN KARAKTERISASI SEDIAAN NANOEMULSI VITAMIN A [Formulation and Characterization of Vitamin A Nanoemulsion] - Annis Catur Adi; Nelly Setiawaty; Atsarina Anindya; Heni Rachmawati (Media Gizi Indonesia, 2019)
Vitamin A is an essential nutrient to support the function of vision, growth, and immune system. Vitamin A cannot be synthesized in the body hence must be obtained through foods or supplements. However, oral administration of vitamin A is often hindered by poor absorption due to its hydrophobic nature and by its easily degradable nature by light and oxygen, particularly at high temperature. This study aimed to prepare a self-assembly vitamin A nanoemulsion with a high loading capacity to improve vitamin A absorption accross intestinal mucosa and to slow down its degradation process. The nanoemulsion was composed by glyceryl monooleate, Cremophor RH-40, and PEG 400 (1:8:1), then titrated with aqueous phase. The nanoemulsion characterization included globule size evaluation, size distribution, zeta potential, globule morphology, entrapment efficiency, physical and chemical stabilities, and ex vivo penetration test on New Zealand albino rabbit intestines. The vitamin A nanoemulsion was found to form transparent and nano-sized emulsions even when loaded with 16.67% vitamin A. The formula also produced 58.1±2.0 nm spherical globules with -0.69 mV zeta potential. Entrapment efficiency of vitamin A in the nanoemulsion was higher than 95%. The nanoemulsion shows stable after storage for 10 days at room temperature, as well as able to increase penetration rate compared to free vitamin A. Taken together, our established vitamin A nanoemulsion has a good stability and was proved to increase vitamin A absorption through intestinal mucosa while simultaneously decreased the vitamin A degradation rate.